PRINSIP ETIKA LINGKUNGAN HIDUP DALAM BUKU CERITA RAKYAT SINGKAWANG 2019 (PENDEKATAN EKOLOGI SASTRA) - Fajria, Nurul; Wirawan, Gunta; Mulyani, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study is to analyze and describe the principles of environmental ethics in the “Buku Cerita Rakyat Singkawang 2019” and describe the implementation of research in Senior High School. This research was conducted on the basis of environmental problems that continue to occur and the existence of folklore that began to fade. The method used in this research is qualitative method with descriptive form. The approach used in this research is literary ecology. Literary ecology in this research is studied through the Sonny Keraf’s principles of environmental ethics. The result of this study show 9 principles of environmental ethic in “Buku Cerita Rakyat Singkawang 2019” with a total of 67 data. The data obtained are 12 principles of respect for nature, 13 principles of responsibility to nature, 10 principles of cosmic solidarity, 5 principles of caring for nature, 4 principles of no harm, 14 principles of living simply and in harmony with nature, 4 principles of justice, 4 principles of democracy, and 4 principles of moral integrity. The implementation of the result of this study is in the form of “Kurikulum Merdeka” teaching module on learning materials related to folklore in grade X Senior High School (SHS), namely on the material of “Hikayat” in Chapter 3: Tracig Values in Stories Across the Eras. The result of this study can be useful as a guide for the community in environmental ethics as well as the preservation of folklore as a culture.